تماثلات المراة الجزائرية في البرامج التلفزيونية - خديجة مشيكل; فاطمة الزهراء بن زيان; د/ ذهبية ايت قاسي (جامعة عمار ثليجي الاغواط, 2024)
ملخصالدراسة: تهدفهذهالمذكرةدراسةتمثلاتالمرأةالجزائريةفيالبرامجالتلفزيونيةذاتالطابعالاجتماعيإلىتحقيقهدفرئيسييتمثلفيرصدوتحليلوتفسيرتمثلاتالمرأةالجزائريةفيالبرامجالتلفزيونيةوالوقوفعلىملامحهذهالبرامجوالعناصرالمكونةلها،إضافةلمعرفةإلىأيمدىيقتربأويبتعدماتقدمالبرامجالتلفزيونيةبالواقعالفعليللمرأةالجزائريةويظهرهذامنخلالالتقديماتوالتشابهاتوالإختلافاتبينمايقدمهالتلفزيون،وماهوسائدفيالواقعالاوضاعالاجتماعيةوالثقافيةوالسياسيةوالاقتصاديةللمجتمعالجزائري واعتمدنافيدراستناعلىالمنهجالمسحيوالعينةالعشوائيةفياختيارناللعينة،تمجمعالبياناتباستعمالتصميماستمارةتحليلمحتوى،حيثتوصلتدراستناالىانهذاالنوعمنالبرامج،ليفاتماتلهتأثيركبيرعلىقيمالمرأةالجزائريةوكانالهدفمنهمعرفةالمعالجةالفنيةالمستخدمةفيبرنامجليفاتماتومعرفةالقوالبالفنيةالتيقدمفيهامضمونالبرنامج. الكلماتالمفتاحية :تمثلاتالمرأةالجزائرية،البرامجالتلفزيونية،المرأةالجزائرية،البرامجالتلفزيونيةذاتالطابعالاجتماعي This memorandum aims to study the representations of Algerian women in television programs of a social nature in order to achieve a main goal, which is to monitor, analyze and interpret the representations of Algerian women in television programs and to identify the features of these programs and their constituent elements, in addition to knowing to what extent they are close or distant to what Television programs present the actual reality of Algerian women, and this appears through the presentations, similarities, and differences between what television presents and what prevails in reality, the social, cultural, political, and economic conditions of Algerian society. In our study, we relied on the survey method and random sampling in selecting the sample. The data was collected using the design of a content analysis form. Our study concluded that this type of program has a significant impact on the values of Algerian women, and its goal was to know the artistic treatment. Used in the Li Fat Mat program and knowing the technical templates in which the content of the program was presented
TVدراسة وصفية تحليلية لعينة من حلقات برنامج لي فات مات على قناة الشروق